Hipovitaminose A em crianças de áreas rurais do semi-árido baiano Vitamin A deficiency in children of rural zones, Northeast region of Brazil - Matildes da Silva Prado; Ana Marlúcia Oliveira Assis; Maisa Cruz Martins; Maria da Purificação Araújo Nazaré; Ioná F. Bonfim Rezende; Maria Ester Pereira Conceição (Universidade de São Paulo, 1995)
Objetivou-se avaliar a distribuição e a magnitude da deficiência de vitamina A e o consumo dietético de 161 crianças de 6 a 72 meses de idade, de áreas rurais do Município de Cansanção-Bahia, Brasil. Os níveis de retinol sérico foram medidos pelo método espectrofotométrico (Bessey-Lowry modificado por Araújo e Flores, 1978). A média do retinol sérico distribuiuse homogeneamente entre as diferentes faixas etárias. Níveis inadequados de retinol sérico (deficiente <10,0 µg/dl e baixos <20,0 µg/dl) foram detectados em 44,7% das crianças, caracterizando a deficiência como problema de saúde pública. Os níveis de retinol sérico não mostraram associação estatisticamente significante com sexo e idade das crianças, contudo as menores de 24 meses apresentaram prevalência mais alta de níveis inadequados. A principal fonte de vitamina A, disponível para essas crianças, é representada pelos carotenóides, em especial beta-caroteno. Foi observada maior diversificação no consumo dos alimentos de conteúdos moderado e baixo em vitamina A no grupo de 24 a 72 meses de idade, sem contudo assegurar níveis adequados de retinol sérico para este grupo etário. The distribution and magnitude of vitamin A deficiency and dietary consumption of 161 children at 6 to 72 months of age in rural zones in Cansanção-Bahia-Brazil were evaluated. The serum retinol levels were measured by the spectrophotometric method (Bassey-Lowry modified by Araújo and Flores). The serum retinol average was found to be distributed homogeneously throughout the different age groups. Inadequate serum retinol levels (<20,0 µg/dl) were detected in 44.7% of the children, which characterized the deficiency as constituting a public health problem. The serum retinol levels showed no statistically significant association as between the sex and age of the children; however the chilfren of less than 24 months showed a higher prevalence of inadequate serum retinol levels. The main available source of vitamin A for these children was represented by carotenoids, especially beta-carotene. Foods regarded as being rich in vitamin A were consumed by all age groups. The greatest diversification of consumption of foordstuffs with moderate and low vitamin A content was observed in the group of children of from 24 to 72 months of age, through this was no guarantee of adequate serum retinol levels in this group however.